Perbandingan Kadar Flavonoid Ekstrak Etanol Daun dan Kulit Buah Alpukat (Persea Americana Mill) - Bida Cincin Kirana; Maria Fatmadewi Imawati; Arinda Eka Aprilia (Yayasan Jompa Research and Development, 2023)
Avocado plants contain secondary metabolites that can be used as herbal treatments for various diseases. The leaves and skin of avocado (Persea americana Mill) contain compounds such as flavonoids, saponins, alkaloids, tannins, terpenoids which are known to be used as antioxidants, anti-inflammatory, and antimicrobial. The purpose of this study was to determine the ratio of flavonoid content of ethanol extract in leaves and fruit skin avocado. Ethanol extract of avocado leaves and rind was obtained by maceration using 70% ethanol solvent, then concentrated using rotary evaporator. Extract in qualitative test using concentrated Mg and HCl powder showed positive red color of flavonoids and then the determination of flavonoid levels using UV-Vis spectrophotometry at a wavelength of 425nm with a variety of concentrations. The results showed that the avocado skin has a higher flavonoid content of 2.4313% W/W compared to avocado leaves that is 1.5289% w/w. This is confirmed by the results of the SPSS test with Independent T-Test obtained a significant value of 0.408 which means that there is a significant difference between the group of ethanol extract of avocado leaves and the group of ethanol extract of avocado skin. Keywords: avocado leaf and skin, ethanol extract, flavonoid content